Perbandingan Analisis Teknikal dengan Pendekatan Moving Average dan Parabolic SAR dalam Memprediksi Pengembalian Saham pada Indeks Saham LQ45 - Isnaini Nuzula Agustin; Fariono Fariono.ong@gmail.com (Ekonomis: Journal of Economics and Business, 2023)
Along with the rapid development of the number of stock investors in Indonesia, technical analysis is needed to assist investors in their efforts to obtain optimal returns. This research was conducted to compare the performance of two types of technical analysis, namely moving average and parabolic sar. This research is a quantitative research with comparative analysis method. The sampling technique used was purposive sampling with the LQ45 index as the research object. The data is monthly data for the LQ45 index in the 2017-2021 period, so a total of 60 observations were obtained. Data analysis includes descriptive statistics and the Kruskal Wallis test. The test results show that there is no significant difference between the performance of the moving average indicator and the parabolic sar indicator. However, the parabolic sar shows higher prediction accuracy compared to the moving average. The results of this study are expected to support investors in choosing good technical indicators, so that they can obtain more accurate stock price prediction results to obtain optimal returns.